Autonomous Gaussian decomposition of the galactic ring survey: I. Global statistics and properties of the 13CO [CO] emission data - Riener, Manuel; Kainulainen, Jouni; Beuther, Henrik; Henshaw, Jonathan D.; Orkisz, Jan H.; Wang, Yifei (Astronomy and astrophysics, 2020)
The analysis of large molecular line surveys of the Galactic plane is essential for our understanding of the gas kinematics on Galactic scales and, in particular, its link with the formation and evolution of dense structures in the interstellar medium. An approximation of the emission peaks with Gaussian functions allows for an efﬁcient and straightforward extraction of useful physical information contained in the shape and Doppler-shifted frequency of the emission lines contained in these enormous data sets. In this work, we present an overview and the ﬁrst results of a Gaussian decomposition of the entire Galactic Ring Survey (GRS) 13CO (1-0) data that consists of about 2.3 million spectra. We performed the decomposition with the fully automated GAUSSPY+ algorithm and ﬁtted about 4.6 million Gaussian components to the GRS spectra. These decomposition results enable novel and unexplored ways to interpret and study the gas velocity structure. We discuss the statistics of the ﬁt components and relations between the ﬁtted intensities, velocity centroids, and velocity dispersions. We ﬁnd that the magnitude of the velocity dispersion values increase towards the inner Galaxy and around the Galactic midplane, which we speculate is partly due to the inﬂuence of the Galactic bar and regions with higher non-thermal motions located in the midplane, respectively. We also used our decomposition results to infer global properties of the gas emission and ﬁnd that the number of ﬁt components used per spectrum is indicative of the amount of structure along the line of sight. We ﬁnd that the emission lines from regions located on the far side of the Galaxy show increased velocity dispersion values, which are likely due to beam averaging effects. We demonstrate how this trend has the potential to aid in characterising Galactic structure by disentangling emission that belongs to the nearby Aquila Rift molecular cloud from emission that is more likely associated with the Perseus and Outer spiral arms. With this work, we also make our entire decomposition results available.
Online veröffentlicht: 24. Dezember
Im Titel ist die Zahl 13 bei 13CO hochgestellt
Gesehen am 09.03.2020